2022
DOI: 10.2147/oajc.s360833
|View full text |Cite
|
Sign up to set email alerts
|

Shared Decision-Making: The Way Forward for Postpartum Contraceptive Counseling

Abstract: There are multi-level barriers that impact uptake of postpartum contraception and result in disparities, including clinical barriers such as provider bias. Fortunately, clinicians have direct control over their contraceptive counseling practices, and thus reducing structural barriers is actionable through high quality contraceptive counseling that equips patients with the knowledge and guidance they need to fulfill their reproductive desires. Yet, many commonly employed contraceptive counseling strategies, lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…Evidence-based practice, supported by best scientific literature and high professional standards, place professionals in a strong position to recommend best practices. [37][38][39][40][41] Historically, health care generally is moving away from a model where this is sufficient to determine the behaviour of both professionals and patients. This approach has been identified with paternalism: it is based exclusively on professional knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence-based practice, supported by best scientific literature and high professional standards, place professionals in a strong position to recommend best practices. [37][38][39][40][41] Historically, health care generally is moving away from a model where this is sufficient to determine the behaviour of both professionals and patients. This approach has been identified with paternalism: it is based exclusively on professional knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Shared decision‐making is one of several approaches that can be used to enhance oral care by optimizing the potential consistency between patients' and professionals' understanding of and acceptance of best approaches to care. Evidence‐based practice, supported by best scientific literature and high professional standards, place professionals in a strong position to recommend best practices 37–41 . Historically, health care generally is moving away from a model where this is sufficient to determine the behaviour of both professionals and patients.…”
Section: Discussionmentioning
confidence: 99%
“…This approach is considered the most ethically sound form of counseling, as it maximizes patient autonomy. Shared decision-making also has clinical benefits, including increased patient satisfaction [11].…”
Section: Sdm and Reproductive Healthmentioning
confidence: 99%
“…2,15 These include socioeconomic and sociodemographic factors such as wealth status, education level, and place of residence, but also restrictive regulations and insurance limitations that inhibit equitable access to contraception and contraceptive counseling. 7,16 Support is provided to institutions for planning and implementing inpatient contraception programs by the Postpartum Contraceptive Counseling Initiative (PCAI) established by ACOG. 17 PCAI offers resources to plan, implement, and sustain inpatient LARC programs and addresses many of the most common barriers to inpatient contraception, specifically LARC, including billing, reimbursement, clinician education, and institutional support.…”
Section: Inpatient Contraception Care Standardsmentioning
confidence: 99%
“…16 In addition to accessibility, concerns have been raised regarding equitability and clinical contraceptive counseling practices. 6,7,9,15,18,19 This is of particular importance given the way pregnant-capable individuals are counseled regarding contraception, which can significantly impact their attitude, choice, and satisfaction with contraception use. Recent studies have shown that person-centered contraceptive care that places an emphasis on the needs and desires of the individual contributes to improved reproductive health outcomes.…”
Section: Inpatient Contraception Care Standardsmentioning
confidence: 99%